IN-VITRO ANTIDERMATOPHYTIC ACTIVITY OF LOW POLAR PETROLEUM ETHER AND INTER POLAR METHANOLIC SEED EXTRACTS OF STERCULIA FOETIDA L. - SHIVAKUMAR SINGH P,; VIDYASAGAR GM, (International Journal of Pharma and Bio Sciences, 2014)
The antidermatophytic activity of interpolar methanolic and low polar petroleum ether soxhlet extracts of Sterculia foetida seed was evaluated by agar well diffusion method, The maximum activity was observed in interpolar methanolic extract against C .albicans followed by E. coli, B. Subtilis, P. aeruginosa, S. aureus, T. rubrum, M.gypseum, T.mentagrophytes and T.tonsurans. When compared to low polar petroleum ether extract. The Minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC), minimum bactericidal concentration (MBC) were determined using broth dilution method. The preliminary phytochemical tests for secondary metabolites were carried out in both the extracts but the results indicated presence of alkaloids, phenols, flavonoids and triterpenoids in the interpolar extract. This study provides a basis for the isolation and purification of anti-dermatophytic compound(s) from the seeds of S. foetida.